1960
DOI: 10.1083/jcb.7.3.493
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopy of Retinal Photoreceptors

Abstract: The fine structure of the cone and rod outer segments of the toad was studied under the electron microscope after fixation in osmium tetroxlde and fixation in formaldehyde followed by chromation. In the OsO4-fixed specimens, the rod outer segment appears to be built of a stack of lobulated flattened sacs, each of which is made of two membranes of about 40 A separated by an innerspace of about 30 A. The distance between the rod sacs is about 50 A. The sacs in the cone outer segment are originated by the folding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1961
1961
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This suggested that the stable Cr(III) ions were kept bound or complexed to oxidized compounds in the retina for at least 2 weeks. Chromation has been used histologically in the retina to stabilize lipid fractions so as to obtain more information about the lipid constituents of visual cells (21, 41–43). Similar to in vivo CrMRI study of myelin lipids in white matter (10), the stability of Cr enhancement in vivo may open further applications of Cr(VI) as a dual marker for in vivo MRI and light microscopy of the retina.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggested that the stable Cr(III) ions were kept bound or complexed to oxidized compounds in the retina for at least 2 weeks. Chromation has been used histologically in the retina to stabilize lipid fractions so as to obtain more information about the lipid constituents of visual cells (21, 41–43). Similar to in vivo CrMRI study of myelin lipids in white matter (10), the stability of Cr enhancement in vivo may open further applications of Cr(VI) as a dual marker for in vivo MRI and light microscopy of the retina.…”
Section: Discussionmentioning
confidence: 99%
“…In consistency with previous studies (17, 18, 20, 45, 46), the highest lipid density across retinal layers appeared in the outer segment of the photoreceptor layer. The outer segments are rich in photoreceptor cells and have many structural similarities as myelin (18, 21). Using Golgi silver staining method upon Cr administration, the photoreceptors were also found to be preferentially stained by Cr in the cephalopod retina (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique may improve the preservation of phospholipids, but it is not of general applicability. One other procedure which will fix unsaturated lipids is formalin fixation-with or without calcium-followed by Baker's (1946) post-chromation (Lasansky & de Robertis, 1960;Casley-Smith, 1963~). This has some advantages over osmium fixation in that the lipid is only slightly electron-dense, and will permit staining with general lipid stains (e.g.…”
Section: Fixationmentioning
confidence: 99%
“…Various analytical methods have been used for the characterization of POSs, including electron microscopy [ 21 , 22 ] and immunostaining [ 21 ]. Corley et al also reported the use of a flow-cytometry-based method to assess the membrane heterogeneity of POS discs [ 23 ], but there have been no reported studies on the characterization of the POS material itself via flow cytometry.…”
Section: Introductionmentioning
confidence: 99%